2012
DOI: 10.1091/mbc.e12-04-0334
|View full text |Cite
|
Sign up to set email alerts
|

The kinesin-3 family motor KLP-4 regulates anterograde trafficking of GLR-1 glutamate receptors in the ventral nerve cord ofCaenorhabditis elegans

Abstract: Cyclin-dependent kinase-5 and the kinesin-3 family motor KLP-4 function in the same pathway to promote anterograde trafficking of glutamate receptors in the ventral nerve cord of Caenorhabditis elegans. This study reveals a cellular control mechanism by which receptor cargo is targeted for degradation in the absence of its motor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 82 publications
3
31
0
Order By: Relevance
“…Our data also suggest a critical role for the motor protein KIF3A in this mechanism. Previous studies demonstrated that various motor proteins of the KIFs exhibit differential function to form intracellular cargo apparatus and regulate protein trafficking, including that of the vascular endothelial growth factor receptor 2 in endothelial cells (34), the glutamate receptor in the ventral nerve cord of Caenorhabditis elegans (worms) (35), and voltage-gated potassium (K v ) channels in mouse hippocampal neurons (36). Specifically, KIF3A mediates the polarized trafficking of K v 1.2 channel to axons (37,38) and the transport of vesicles containing -catenin toward the plasma membrane in the developing neuroepithelium (39).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggest a critical role for the motor protein KIF3A in this mechanism. Previous studies demonstrated that various motor proteins of the KIFs exhibit differential function to form intracellular cargo apparatus and regulate protein trafficking, including that of the vascular endothelial growth factor receptor 2 in endothelial cells (34), the glutamate receptor in the ventral nerve cord of Caenorhabditis elegans (worms) (35), and voltage-gated potassium (K v ) channels in mouse hippocampal neurons (36). Specifically, KIF3A mediates the polarized trafficking of K v 1.2 channel to axons (37,38) and the transport of vesicles containing -catenin toward the plasma membrane in the developing neuroepithelium (39).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through GLR-1 controls the rate at which animals reverse during spontaneous locomotion (Zheng et al, 1999). Mutants with reduced glutamate signaling, such as glr-1 null mutants or animals lacking the vesicular glutamate transporter eat-4 /VGLUT, exhibit decreased reversal frequencies (Brockie et al, 2001; Burbea et al, 2002; Zheng et al, 1999), whereas mutants with increased GLR-1 signaling exhibit a higher rate of reversals (Burbea et al, 2002; Juo and Kaplan, 2004; Juo et al, 2007; Schaefer and Rongo, 2006; Zheng et al, 1999, Monteiro et al, 2012). We found that the spontaneous reversal frequency of daf-8 and daf-7 mutant animals is significantly higher than in wild type animals (Figure 7 A), consistent with increased signaling through GLR-1 receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle-independent roles of CDK5 have been identified in a mammalian nervous system (Su and Tsai 2011). Interestingly, C. elegans CDK-5 is also required for neuronal functions (Ou et al 2010; Park et al 2011; Goodwin et al 2012; Monteiro et al 2012). Further, C. elegans CDK-8 regulates axon navigation decisions in the nervous system (Steimel et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans , CDK-5 regulates polarized trafficking of presynaptic components and dense-core vesicles (Ou et al 2010; Goodwin et al 2012). CDK-5 is also required for synapse elimination and formation (Park et al 2011), and for trafficking of glutamate receptors in the ventral nerve cord (Monteiro et al 2012). CDK-8 is required for axon navigation decisions in neurons (Steimel et al 2013), and also functions in vulval development by regulating the epidermal growth factor receptor-Ras-extracellular signal-regulated kinase pathway (Grants et al 2016).…”
mentioning
confidence: 99%